PENANGANAN ANAK SEBAGAI PELAKU TINDAK PIDANA NARKOBA MELALUI DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK - Eka Dewi Kartika; Salma Laitupa (The Juris, 2020)
Juvenile criminal justice is one of the main duties of a public justice institution in a country that examines and decides criminal cases of children, both as witnesses, victims and perpetrators are children who are faced with the law. the problem that is the reason why children behave in violation of criminal law and implement steps to prevent this behavior.